Pengaruh Return On Assets, Non Performing Loan, Dan Loan To Deposit Ratio Terhadap Capital Adequacy Ratio Pada Bank Konvensional Di Indonesia - Francis Marlim dan Ignatius Roni Setyawan (Universitas Tarumanagara, 2019)
Capital Adequacy Ratio becomes an indicator to assess the good performance of a bank, in carrying out its business activities every bank will strive to generate optimal capital. The purpose of this study is to analyze the effect of profitability,asset quality, and liquidity on capital and theory that can explain the reasons banks need a big capital. The population in this research is a number of 20 group of conventional bank book 1 until book 4 from 2011 to 2016 in Indonesia Stock Exchange. Analysis using the panel regression with Generalized Least Square (GLS) method is used to test their hypothesis. The analysis find that first Return on Assets have relationship to Capital Adequacy Ratio significantly on banking companies. Second, Non Performing Loan have relationship to Capital Adequacy Ratio significantly on banking companies. Third, Loan to Deposit Ratio have relationship to Capital Adequacy Ratio significantly on banking companies. Based on results, author suggest to do more research on the other variables in order to have another models